2020
DOI: 10.1039/d0dt02526g
|View full text |Cite
|
Sign up to set email alerts
|

A mechanochromic cyclemetalated cationic Ir(iii) complex with AIE activity by strategic modification of ligands

Abstract: Two new aggregation-induced emission (AIE)-active cyclemetalated cationic Ir(III) complexes have been rationally designed and synthesized by introducing O-H substituents into the Schiff base ligands. π-Hydrogen bonding is successfully exploited for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Under mechanical stimulation, the change of interactions lead to the change of stacking modes, resulting in the mechanochromism. Pei and Zhao' group prepared a series of cationic Ir(III) complexes with significant mechanochromic luminescence (Pei et al, 2020;Zhao et al, 2021). For the first time, the hydroxyl substituents were introduced into Ir mechanochromism.…”
Section: Mechanochromism Of Iridium Metal-organic Compounds Mononucle...mentioning
confidence: 99%
See 1 more Smart Citation
“…Under mechanical stimulation, the change of interactions lead to the change of stacking modes, resulting in the mechanochromism. Pei and Zhao' group prepared a series of cationic Ir(III) complexes with significant mechanochromic luminescence (Pei et al, 2020;Zhao et al, 2021). For the first time, the hydroxyl substituents were introduced into Ir mechanochromism.…”
Section: Mechanochromism Of Iridium Metal-organic Compounds Mononucle...mentioning
confidence: 99%
“…Although the current research on mechanochromic metal-organic compounds is limited, such mechanochromic materials are still attractive and are expected to exhibit more interesting phenomena due to the metalophilic interactions existed in metal complexes. These mechanochromic phenomenons are thought to result from the crystalline-to-amorphous (CA) phase transformation, single-crystal-to-single-crystal (SCSC) phase transformation or triplet excited states transformation caused by the intermolecular conformational folding or twisting, as well as changes in intermolecular π-π, metalophilic or hydrogen-bonding interactions (Seki et al, 2013;Ito et al, 2013;Seki et al, 2015;Jin et al, 2017;Jin et al, 2018;Li et al, 2019;Pei et al, 2020;Xie et al, 2020). Indeed, an explicit mechanism has not been investigated yet because of the difficulty in characterizing the amorphous phase.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, AIEgens have unique aggregation-enhanced theranostics (AET) properties, referring to the advantages of enhancements in ROS generation, nonlinear optical effects under aggregation-induced effects [ 21 , 22 ]. On the other hand, many cases of Ir(III) complexes with AIE properties have been reported to date [ 23 , 24 , 25 , 26 ] and the following design strategies are generally recommended: (i) introducing active units with AIE properties into Ir(III) complexes and (ii) restricting intramolecular motion of flexible rotating units (such as imine bonds of Schiff bases) through coordination with the central metal iridium. Ir(III) complexes are potential phosphorescent molecules for the construction of AIE materials via strategic modification of ligands [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] Although some research studies on the stimulus-responsive properties of AIE/AIEE compounds have been reported, most of them focus on a single-stimulus response. [35][36][37] To broaden the scope of practical applications, we need to design multi-stimuliresponsive materials with multicolor and high-contrast, and deeply explore the relationship between their structure and properties.…”
Section: Introductionmentioning
confidence: 99%